Comparative study of waqf signs between the Qur’anic Manuscripts of Medina and al-Quddus, Indonesia - Muhammad Ainun Na’im (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2023)
Reciting the Qur'an is an essential worship for Muslims. Reciting it is worth merit if it is recited correctly according to the rules of tartil (in proper order). One of the components of tartil is knowing a good place to stop in reciting the Qur'an so that, it is not mistaken in the meaning intended in it. The Muslim community has confusion when recite one manuscript of the Qur'an with a particular waqf sign(to stop recitation in the end of word) and then recite another manuscript of the Qur'an with a different waqf sign. In this study, the researchers describe what mazhab (school) of waqf ibtida' is used in various famous manuscripts worldwide and Indonesia. Then provide a comparison of the sign of waqf in QS. al-Qashash, which is in the Medina manuscripts and al-Quddus manuscripts. This study uses a library research with descriptive-comparative method by comparing the two manuscripts of the Qur'an about the existing waqf ibtida' mazhab. It was found that there were differences in the placement of the place waqf along with the sign of the waqf. And from these two Qur'an mushafs, each has a basis to take place and sign of waqf which can be accounted for.